Impact of adverse childhood experiences on the symptom severity of different mental disorders: a cross-diagnostic study. Issue 2 (22nd April 2022) - Gu, Wenjie; Zhao, Qing; Yuan, Chengmei; Yi, Zhenghui; Zhao, Min; Wang, Zhen
Abstract : Background: Adverse childhood experiences have a significant impact on different mental disorders. Objective: To compare differences in adverse childhood experiences among those with different mental disorders and their relationships in a cross-disorder manner. Methods: The study included 1513 individuals aged ≥18 years : 339 patients with substance use disorders, 125 patients with schizophrenia, 342 patients with depression, 136 patients with bipolar disorder, 431 patients with obsessive-compulsive disorder (OCD), and 140 healthy controls. The Early Trauma Inventory Self Report-Short Form was used to investigate childhood traumatic experiences, and the Addiction Severity Index, Positive and Negative Syndrome Scale, Hamilton Depression Scale, Young Mania Rating Scale, and Yale-Brown Obsessive-Compulsive Scale were used to assess mental disorder severity. Correlation and multivariate logistic regression were analysed between adverse childhood experiences and clinical features. Results: Levels of adverse childhood experiences were significantly different among different mental disorders. Moreover, 25.8% of patients with substance use disorders reported childhood trauma, which was significantly higher than found in the other four psychiatric disorder groups. Emotional abuse scores were positively correlated with disease severity: the higher the total trauma score, the more severe the mental disorder. Conclusions: Adverse childhood experiences are a common phenomenon in those with mental disorders, and the level of trauma affects mental disorder severity. Emotional abuse is closely related to many mental disorders. The incidence or severity of mental disorders can be reduced in the future by reducing the incidence of adverse childhood experiences or by timely intervention in childhood trauma.